1.146. Rozwiąż równania: a) log4 (x + 3) – 2 = log4 (x – 1) – log4 8 b) log (x – 3) – log (2 – x) = log (x ^ 2 – 4) b) loe, (2x ^ 2 + 4x – 6) = 2 d) log1 (x + 2)/x = 1 log1 16 = 2 b) log2 (log8 x) = 1 d) log2 [1 – log3 (x + 4)] = 1 f) log 6 \ 1+log 3 [1+log 2 (x+3)]\ = 1 2 log1/2 log1 (x ^ 2 – 2x)/(x – 3) = 0 h) c) log 5 + log (x + 10) = 1 – log (2x – 1) + log (21x – 20) d) log5 (3x – 11) + log5 (x – 27) = 3 + log3 8 Rozwiąż równania: a) 2 * log3 (x – 5) – log3 4 = log3 (3x – 20)

1.146. Rozwiąż równania: a) log4 (x + 3) – 2 = log4 (x – 1) – log4 8 b) log (x – 3) – log (2 – x) = log (x ^ 2 – 4) b) loe, (2x ^ 2 + 4x – 6) = 2 d) log1 (x + 2)/x = 1 log1 16 = 2 b) log2 (log8 x) = 1 d) log2 [1 – log3 (x + 4)] = 1 f) log 6 \ 1+log 3 [1+log 2 (x+3)]\ = 1 2 log1/2 log1 (x ^ 2 – 2x)/(x – 3) = 0 h) c) log 5 + log (x + 10) = 1 – log (2x – 1) + log (21x – 20) d) log5 (3x – 11) + log5 (x – 27) = 3 + log3 8 Rozwiąż równania: a) 2 * log3 (x – 5) – log3 4 = log3 (3x – 20) 

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz